ANALISIS ALOKASI BIAYA OVERHEAD PABRIK ATAS PENENTUAN HARGA POKOK PRODUKSI PADA PT BUMI KENCANA INDUSTRI - Handoko, Karina; Rasyid, Ardiansyah (Jurnal Paradigma Akuntansi, 2024)
This studie aims to dettermine the effect,of factory overrhead cost allocation, in determning the costt of production at PT. BUMI KENCANA INDUSTRY. This research method is a descriptive quantitative approach. This study intends to analyze the alocation of factor overhed costs in determining the Cost of Production at PT. Bumi Kencana Industry. Researchers used data from 2019-2020 as the year used in the study. The discover in this study, indicate that the allocation of factory overhead costs from PT. Bumi Kencana Industri based on the amount of raw materials is less effective. This is shown in the figures obtained in 2019 which is 86.6% and in 2020, which is 82.46%. In addition, the effectiveness of the BOP allocation also decreased in 2020, indicating a decrease in the effectiveness of the company's activities.